Conformations and spectroscopic properties of laccaic acid A in the gas phase and in implicit water - Supaporn Dokmaisrijan (2018)
Conformations and spectroscopic properties of laccaic acid A (lacA) were studied by means of the experimental and theoretical approaches. The minimum energy conformers of lacA in the gas phase and in implicit water obtained from the B3LYP/6-311G(d,p) calculations displayed the same orientation of the COOH and OH groups on the anthraquinone-based component. The intramolecular hydrogen bonds (H-bonds) formed between the COOH, CO and OH groups are very strong. In contrast, the orientations of the Ph(OH)CH 2 CH 2 NHCOCH 3 substituent moiety on the anthraquinone-based component in the gas phase and in implicit water are completely different. The substituent prefers to bind with the anthraquinone-based component in the gas phase while it moves away from the anthraquinone-based component in implicit water. The calculated IR spectra of the two lowest-lying energy conformers of lacA in the gas phase fit to the experimental FTIR spectrum. The full assignments of the vibrational modes with the correlated vibrational wavenumbers of those conformers were proposed here, for the first time. The intramolecular H-bond formations in lacA can cause the shift of the vibrational wavenumber for the COOH, CO, OH and NH groups as compared to the normal vibrations of these groups. The NMR spectra showed that the stabilities of the two lowest-lying energy conformers of lacA in the gas phase are comparable and this is consistent with their computational energies. The UV-Vis spectra of the lowest-lying energy conformers of lacA in implicit water were compared with the experimental UV-Vis spectrum. The calculations suggested that the electronic transition in the visible region involves with the singlet π → π - excitation which the electron density transfers to a COOH group on the anthraquinone ring. © 2012 Elsevier B.V. All rights reserved.